Optimising control of microwave plasma bias enhanced nucleation for heteroepitaxial chemical vapour deposition diamond - Marshall, R; Whitfield, MD; Tracey, S; Thompson, D; Foord, J; Jackman, R (1997)
Bias enhanced nucleation (BEN) during microwave plasma enhanced chemical vapour deposition of diamond on Si(100) has been studied using atomic force microscopy (AFM), scanning electron microscopy, Raman scattering and optical reflectivity measurements. The critical nature of the BEN treatment period in the formation of nuclei that subsequently lead to high quality oriented films has been demonstrated. An effective technique is described for determining when optimal BEN treatment has been carried out on Si substrates which should be independent of the reactor in use. © 1997 Elsevier Science S.A.